1999
DOI: 10.1016/s0886-3350(99)80017-0
|View full text |Cite
|
Sign up to set email alerts
|

Axial length and posterior staphylomain Saudi Arabian cataract patients

Abstract: Posterior staphyloma was present in a high percentage of Saudi Arabian patients having cataract extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Longer AXL and chorioretinal atrophy had close relationships with posterior staphyloma in high myopia. [9][10][11] Posterior staphyloma is recognized as an important factor in foveoschisis and foveal detachment without a macular hole. 7,8 Longer AXL, chorioretinal atrophy, and posterior staphyloma represent the outer ocular pouching forces resulting in pathologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Longer AXL and chorioretinal atrophy had close relationships with posterior staphyloma in high myopia. [9][10][11] Posterior staphyloma is recognized as an important factor in foveoschisis and foveal detachment without a macular hole. 7,8 Longer AXL, chorioretinal atrophy, and posterior staphyloma represent the outer ocular pouching forces resulting in pathologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was reported to be 0.7% in the Blue Mountains Eye Study, 0.8% in the Handan Eye Study, and 1.6% in the Beijing Eye Study 21 23 . Further, it was reported to be 0.1% among Singaporean children aged 12–16 years 24 and 10.7% in patients with cataract in Saudi Arabia 25 . These reports suggest that the prevalence should be examined in association with age, sex, axial length (AL), and refractive error.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 The prevalence of posterior staphyloma varies depending on the study and the population analysed. For example, it has been found a 0.7% in the Blue Mountains Eye Study 4 (n=3654, age ≥49 years), a 0.8% in the Handan Eye Study 5 (n=6830, age ≥30 years), a 1.6% in the Beijing Eye Study 6 (n=4439, age ≥40 years), a 0.1% in Singaporean children 7 (n=1227, age 12-16 years) or a 10.7% in Saudi Arabia cataract patients 8 (n=629, age ≥40 years). A recent study carried out by Numa et al 9 indicated that the calculated prevalence in highly myopic eyes varies from 19% to 90%.…”
Section: Introductionmentioning
confidence: 99%